Quantitative ultrasound at the hand phalanges in patients with bisphosphonate-related osteonecrosis of the jaws - Fragoso Motta, Ana Carolina; Macedo, Leandro Dorigan de; Santos, Gisele Guimaraes [UNESP]; Guerreiro, Carlos Tostes; Ferrari, Tatiane; Leitao de Oliveira, Thais Feitosa; Silva Santos, Paulo Sergio da; Oliveira-Santos, Christiano de; Alves Ricz, Hilton Marcos; Xavier, Samuel Porfirio; Iannetta, Odilon (Sociedade Brasileira De Pesquisa Odontologica, 2015)
Patients with bisphosphonate-related osteonecrosis of the jaws (BRONJ) who received intravenous or oral bisphosphonates (BP) were selected for determination of their bone microarchitecture as a risk predictor of BRONJ development. The diagnosis of BRONJ was made based on clinical and radiographic findings. The control group consisted of healthy patients. All patients underwent quantitative and qualitative ultrasound measurements of bone at the hand phalanges carried out using the DBM Sonic BP. Ultrasound bone profile index (UBPI), amplitude-dependent speed of sound (AD-SoS), bone biophysics profile (BBP), and bone transmission time (BTT) were measured. The BRONJ group consisted of 17 patients (62 +/- 4.24; range: 45-82); 10 (58.8%) were male and seven (41.1%) were female, of whom 11 (64.7%) suffered from multiple myeloma, three (17.6%) from osteoporosis, one (5.8%) from prostate cancer, one (5.8%) from kidney cancer, and one (5.8%) from leukemia. Fourteen (82.3%) of them received intravenous BP whereas three (17.6%) received oral BP. Nine (9/17; 52.9%) patients developed bone exposure: two in the maxilla and seven in the mandible. Regarding quantitative parameters, Ad-SoS was low in the BRONJ group, but not significant. The UBPI score was significantly reduced in BRONJ patients with exposed bone when compared to controls (0.47 +/- 0.12 vs. 0.70 +/- 0.15; p = 0.004). The present study demonstrated that quantitative ultrasound was able to show bone microarchitecture alterations in BRONJ patients, and suggests that these analyses may be an important tool for early detection of bone degeneration associated with BRONJ.
Keywords: Bisphosphonate-Associated Osteonecrosis of the Jaw; Dental Care; Ultrasonography; Bone Density